2015
DOI: 10.1002/hyp.10604
|View full text |Cite
|
Sign up to set email alerts
|

The hydrology of interconnected bog complexes in discontinuous permafrost terrains

Abstract: In the zone of discontinuous permafrost, the cycling and storage of water within and between wetlands is poorly understood. The presence of intermittent permafrost bodies tends to impede and re‐direct the flow of water. In this region, the landscape is characterized by forested peat plateaus that are underlain by permafrost and are interspersed by permafrost‐free wetlands. These include channel fens which convey water to the basin outlet through wide, hydraulically rough channels and flat bogs which are typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 48 publications
(80 reference statements)
4
92
0
Order By: Relevance
“…The effect observed here is conceptually similar to the observations on larger scale as described by Connon et al (2015), who 5 focused on the interconnectivity of wetlands. The flow on the top of the permafrost follows a fill and spill behaviour that is similar to the processes occurring on hillslopes with bedrocks topography (Wright et al, 2009).…”
Section: Solute Transport In the Active Layersupporting
confidence: 89%
“…The effect observed here is conceptually similar to the observations on larger scale as described by Connon et al (2015), who 5 focused on the interconnectivity of wetlands. The flow on the top of the permafrost follows a fill and spill behaviour that is similar to the processes occurring on hillslopes with bedrocks topography (Wright et al, 2009).…”
Section: Solute Transport In the Active Layersupporting
confidence: 89%
“…Although isolated collapse scars are large in number, they account for less than 5% of the Scotty Creek 5 catchment, while the area occupied by connected collapse scars is more than five times larger and roughly equivalent to the area occupied by channel fens (Quinton et al, 2009a). This conceptualisation of the form and hydrological functioning of collapse scar wetlands was modified again by Connon et al (2015) who demonstrated that many of these features that were assumed to be hydrologically isolated, can form ephemeral connections with a fen (either directly or via another collapse scar or series of them) during periods of high moisture supply, such as during the snowmelt runoff period. (A more detailed 10 discussion on the development and hydrological functioning of such connections is presented below in the context of permafrost thaw).…”
Section: Landscape Characterisation and Functioningmentioning
confidence: 99%
“…This process the authors referred to as 'bog capture' transforms internally drained bogs to 'open bogs' that are 5 hydrologically connected to fens. Bog capture increases basin runoff by adding to it the runoff from direct precipitation onto captured bogs, and the runoff entering such bogs from their local contributing areas, termed "bogsheds" (Connon et al, 2015). As captured bogs expand due to permafrost thaw at their margins, they merge into other bogs, a process that further expands the basin runoff contributing area, and therefore basin runoff as well.…”
Section: Scotty Creek In Transitionmentioning
confidence: 99%
See 2 more Smart Citations